A cultural learning approach to acculturation : teaching and learning between native English-speaking teachers and university students in Southwest China : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Communication at Massey University, Wellington, New Zealand - Zhou, Zhidan (Massey University, 2025)
The globalisation of education has affected the teaching dynamics of native English-speaking teachers (NESTs) in the Chinese higher education system. The roles of NESTs are challenging and require a nuanced understanding of teaching effectiveness, cultural intelligence (CQ), and leadership in higher education. This study explores the complex and dynamic roles of NESTs in Chinese higher education, focusing on their teaching practices, CQ, and leadership contributions. Forty-five Chinese students, 15 NESTs and five Chinese university leaders (CULs) from Southwest China participated in semi-structured interviews. Findings highlight that the pedagogical practices of NESTs were viewed positively for practical language application but criticized for being culturally incompatible. Instructional outcomes showed that perceived immediacy positively influenced affective and behavioral learning but did not affect cognitive learning. In addition, CQ plays a crucial role in shaping NESTs’ teaching strategies, classroom engagement, and adaptability to diverse learning needs. Participants who described CQ-aligned practices reported more adaptive teaching and richer student participation. NESTs play an important leadership role in improving students' language skills and cultural knowledge. NESTs are credited with providing authentic language environments, innovative teaching methods, and cultural insights that enhance students’ language and cultural understanding. Despite these positive contributions, NESTs have faced various challenges in their leadership role. This study emphasizes the need for culturally responsive teaching, professional development for NESTs, and collaboration between NESTs and institutions, deepens the understanding of NESTs’ contributions to instructional communication, and offers suggestions for improving intercultural communication in global academic contexts
Articles One & Three comprising Chapter Four were removed as they are copyrighted to their respective publishers, but they may be accessed from the links on p. viii.
Keywords: instructional belief model, cultural intelligence, leadership roles, native speakerism, native English-speaking teachers, intercultural communication, instructional communication; Education, Higher; China; English teachers; College students; Attitudes; Education and globalization; Cross-cultural studies; Intercultural communication in education; 390303 Higher education; 470212 Multicultural, intercultural and cross-cultural studies